Animal models to study the pathogenesis and novel therapeutics of oral lichen planus - Choi, Youngnim (Frontiers in Oral Health, 2024)
Oral lichen planus (OLP) is a prevalent oral mucosal disease characterized by an unknown etiology and a complex pathogenesis. Patients with OLP endure a chronic course marked by alternating non-erosive and erosive lesions, with no definitive cure currently available. Particularly challenging is the treatment of recalcitrant erosive OLP, highlighting an urgent need for therapies targeting specific pathogenic pathways. In diseases like OLP, where the etiopathogenesis is intricate and elusive, animal models are indispensable for hypothesis testing and elucidating disease mechanisms. To date, only three animal models for oral lichenoid lesions have been reported in the literature. This Perspective paper evaluates these existing models, along with a novel OLP mouse model introduced at the 3rd International Conference on Oral Mucosal Immunity and Microbiome. The validity of these models is critically assessed, and their potential future applications in advancing our understanding of OLP are discussed.